Pengaruh Corporate Social Responsibility, Leverage, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan (Studi Pada Perusahaan Manufaktur Sub Sektor Food & Beverage Yang Terdaftar Di BEI Tahun 2017-2019) - Rifa Royhanah el Somita; Muhammad Agus Salim; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the effect of the independent variables, namely corporate social responsibility, leverage and company size on the dependent variable, namely the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2017-2019 period. The method for sampling using purposive sampling based on predetermined criteria. The number of samples is 20 manufacturing companies. The data in this study used simple linear regression and hypothesis testing.The results of this study indicate that corporate social responsibility shows no significant positive effect on financial performance of peer companies, leverage has a negative and significant effect on corporate financial performance, firm size shows no significant positive effect on corporate financial performance. Keywords: Corporate social responsibility, leverage, company size and financial performance